Drug-induced acute kidney injury: a cohort study on incidence, identification of pathophysiological mechanisms, and prognostic factors - Garcia, Georgia [UNESP]; Pacchini, Vinicius Repetti [UNESP]; Zamoner, Welder [UNESP]; Balbi, Andre Luis [UNESP]; Ponce, Daniela [UNESP] (Frontiers, 2024)
Introduction: Acute Kidney Injury (AKI) is a common clinical syndrome characterized by an abrupt decline in the glomerular filtration rate (GFR), which can cause severe alterations in blood volume and acid-base balance. Drug-Induced Acute Kidney Injury (DI-AKI) is associated with exposure to nephrotoxic medications, particularly among hospitalized patients. Adverse drug reactions comprises type A and type B reactions. Type A reactions are predictable based on the pharmacology of the substance, dose-dependent, and manifest as Acute Tubular Necrosis (ATN). Type B reactions are unpredictable, idiosyncratic, not dose-dependent, and manifest as Acute Interstitial Nephritis (AIN), Crystal-Induced Nephropathy, among others. Objective: To evaluate DI-AKI incidence, identify the main associated drugs and the pathophysiological mechanism of the observed injury, analyze prognostic factors associated with unfavorable outcomes, and compare the outcomes of death and the need for Acute Kidney Support Therapy (AKST) between patients with DI-AKI vs. AKI due to other etiologies. Methods: A retrospective cohort study conducted at the Hospital das Clínicas of the Faculty of Medicine of Botucatu – UNESP (HC-FMB), using data from patients hospitalized between January 2016 and April 2022 and followed, via consultation, by the AKI-Nephrology team. Inclusion criteria: diagnosis of AKI and Chronic Kidney Disease (CKD) with superimposed AKI. Exclusion criteria: patients under 18 years old or on chronic Renal Replacement Therapy. AKI was diagnosed based on creatinine increase as established by KDIGO 2012. Data were presented as mean and standard deviation or median with interquartile range and frequency. Statistical significance was set at 5% (p < 0.05). Comparative analyses were performed using the Chi-Square test for categorical variables and the T-test for continuous variables. Subsequently, logistic regression was performed to identify factors associated with the need for AKST and death. Results: A total of 1,398 patients were analyzed, most of them males (61.4%), with a mean age of 64 years ±14.4 years. The most prevalent etiology of AKI was Mixed Ischemic + Septic AKI (28%). DI-AKI was a significant cause of AKI (19.3%). Of these, 25.2% were isolated DI-AKI and 74.8% were Mixed DI-AKI + Ischemia and/or Sepsis. Among patients with DI-AKI, the mean age was 61.15 ± 15.26, males were the most frequent, the majority were not subjected to AKST and survived. Most of these patients were hospitalized in the ward, did not need vasoactive drugs, nor did they use mechanical ventilation. DI-AKI showed lower severity and mortality compared to other AKI etiologies but had a similar need for AKST (26.3% vs. 35.4%, p < 0.05 and 31.8% vs. 36.8%, p > 0.05). Most nephrotoxic drugs caused type A reactions, with Vancomycin being the primary nephrotoxin. Among drugs associated with DI-AKI, Vancomycin was associated with a higher need for AKST and death, while Amphotericin B was associated with a lower risk of AKST and death. Conclusion: Although the mortality rate is lower among DI-AKIs compared to other AKI etiologies, the need for AKST was similar. Therefore, it is recommended that DI-AKI be recognized early to enable dose reduction or even drug suspension, depending on the type of reaction, to reduce healthcare costs and improve clinical outcomes for patients.
Keywords: AKI (acute kidney injury); DI-AKI (drug-induced acute kidney injury); incidence; nephrotoxicity; prognosis